The impact of soft regulations on boardroom diversity and shareholders' confidence in Malaysia - Rahman, H.U. (Institute of Electrical and Electronics Engineers Inc., 2015)
Soft regulations, commonly known as Corporate Governance (CG) codes, aim to enhance shareholders' confidence by regulating corporate world. These regulations have turned much of the attention towards the improvement of boardroom diversity particularly after economic turmoil 2007-08. Malaysia like other countries, also recommended improving boardroom diversity in its recently introduced third CG code (Malaysian Code on Corporate Governance) in 2012. Thus, this paper proposes to investigate boardroom diversity (age, gender & ethnicity) and its relation with shareholders' confidence measured by share market price in the non-financial listed companies of Malaysia from 2010 to 2013. The proposed period of analysis represents two years pre and two years post enactment period of the code which will highlight the impact of the code, if any. The proposed study will fill the literature gap as most of the previous literature in the area has investigated the relationship between boardroom diversity and firm performance rather than shareholders' confidence. Â© 2015 IEEE.